PENGARUH KEPATUHAN HUKUM PERUSAHAAN TERHADAP KINERJA KEUANGAN PERUSAHAAN DI INDONESIA - Bagas Tarigan (JURNAL PENDIDIKAN, HUMANIORA, LINGUISTIK DAN SOSIAL (JAGADDHITA), 2024)
Company law has a very important role in regulating and ensuring business operations run in accordance with applicable regulations. In Indonesia, company law covers various aspects, from establishment, governance, to protection of shareholders and other interested parties. Company legal compliance not only functions as a form of fulfilling legal obligations, but also as a factor that can influence the sustainability and financial performance of a company. Companies essentially function as a forum for entrepreneurs to gain profits. The research method used in this research is descriptive analysis, because it is based on the provisions governing the influence of company legal compliance on the financial performance of companies in Indonesia. Legal compliance has a significant impact on a company's financial performance. Companies that comply with legal regulations tend to be more financially stable, as they avoid the risks associated with breaking the law, such as fines, sanctions and reputational harm.